The Effect of Giving Human Umbilical Cord Mesenchymal Stem Cells (HUMSC) on the Expression of Collagen I in Menopause Model Mice - Marta, Kadek Fajar; AAN Jaya Kusuma; Ida Bagus Aditya Mayanda; IB Yudhistira Anantasurya Vidhisvara; Juventius Anggoa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Patients with pelvic floor dysfunction (PFD) who fail conservative treatment will undergo surgery. In recent years, various therapeutic approaches for PFD using stem cells have been investigated in vivo. One component of stem cells is the human umbilical cord mesenchymal stem cell (HUMSC). It is hoped that HUMSC can modify the collagen and elastin content in the extracellular matrix, leading to improvements in pelvic floor strength and PFD. Methods: This research is an experimental study with a randomized posttest-only controlled group design with the aim of determining the effect of giving HUMSC on the expression of Collagen I in a female mouse model of menopause. There are inclusion criteria, namely female Balb/c mice, healthy, never mated, aged 8 - 12 weeks, and body weight 18 - 22 grams. The research will be carried out with statistical analysis using SPSS; a p-value <0.05 is considered significant. Results: The results of the analysis of the distribution of sample means show that there are significant differences between the two groups. The treatment group had a higher mean expression of type I collagen compared to the control group. In addition, variation in the control group was lower compared with the treatment group, which could be interpreted as higher consistency in the response to HUMSC treatment. Conclusion: Human umbilical cord (HUMSC) has a positive impact on type I collagen expression in menopausal model mice.